Various Strategy in Teaching English Through Literature in Senior High School - Ulul Azmi, Muhammad Bunayya; Maram, Mohammad Aufal; Rohmana, Wahyu Indah Mala (Journal of English for Academic and Specific Purposes (JEASP), 2023)
Learning English through literature is one of the various ways to improve our English since it includes many aspects, speaking and listening that are used in daily interaction, and reading skills that cannot be separated from literacy. Various way of teaching method and strategies has been developed in the past few years. Based on the previous explanation, the researchers want to find out the kinds of literature (drama, short stories, novels, song) being taught in the class, and what method is used by the teacher. the school teaching program has already used some kinds of literature in teaching and learning activities. Since there are some branches in literature, the teacher mentioned that the one used are drama, song, and narrative text (poems, short stories, novels). The aim of using this strategy is to strengthen the relationship between two different aspects of educational pioneers so both of them could support and embrace their differences.